Sustainability education - A challenge for South-East Asia and Europe. - Kaerchner-Ober, Renate; Dippel, Uwe (Science Publications, 2011)
Problem statement: South-East Asia and Europe face rapid changes in social, economical and political terms. Though starting points are different, both regions experience similar problems. We see a strong slowdown of economic growth; changing proportions of the population through migration, natural disasters, economic reasons and aging populations. Problems and conflicts occur in the first decade of the new millennium, as a lot of changes in the educational sector have been undertaken. This study deals with sustainability education in both regions. Approach: In particular, we compare issues of higher education in Malaysia and Germany. We explore current tendencies and changes from various perspectives and how they fit into a concept of sustainability education. (Or is it education to sustainability, respectively sustainable education?) Results: It is shown, that sustainability in the educational field is possible only, if related to a socio-cultural context that considers the disposition of the individual; instead of using assumptions gathered and subsequently transferred from a society distinct in its predominant descriptors, respectively from determinators of some abstract industrial process demands. Conclusion: Sustainable education is recognized as a not a priori transferable entity in the global context. It must rather be contextualized and suitably embedded into individual and divers societal environs.